2016
DOI: 10.4028/www.scientific.net/kem.722.311
|View full text |Cite
|
Sign up to set email alerts
|

Dosage of Metakaolin in High Performance Concrete

Abstract: This article deals with optimal dosage of metakaolin as addition in high performance concrete. The main criteria for assessing the optimal dosage of metakaolin was compressive strength, rheological behaviour and economic benefits. Metakaolin was added to the mixture of high performance concrete in the range from 0 to 25% weight of cement. The comparison of metakaolin and microsilica, which is often used by concrete producers due to its excellent properties, is also performed in this article. The experiments sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
(5 reference statements)
1
5
0
Order By: Relevance
“…• the optimal amount of SCM is close to 10%, which was also found in other studies [28], • the strength increase, caused by the SCMs, is the highest at 28 days of age. After that, in all cases, a proportionally smaller strength increase was measured.…”
Section: Research Objectivessupporting
confidence: 87%
“…• the optimal amount of SCM is close to 10%, which was also found in other studies [28], • the strength increase, caused by the SCMs, is the highest at 28 days of age. After that, in all cases, a proportionally smaller strength increase was measured.…”
Section: Research Objectivessupporting
confidence: 87%
“…Our aim was to collect a large database and, therefore, all test results of mechanical properties of concrete with MK conducted based on international standards were collected for use in this study. This database was collected from 45 published studies [ 4 , 15 , 16 , 17 , 18 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] and is shown in the supplementary document . In the supplementary document, Tables S1–S3 contain the information of input parameters and output for , …”
Section: Data Collectionmentioning
confidence: 99%
“…Table S3: Experimental database of FS of concrete with metakaolin. References [ 4 , 15 , 16 , 17 , 18 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 72 , 73 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%
“…There are many researchers who investigated the effect of metakaolin on the properties of concrete. It was found that the optimal dosage of metakaolin as additive in high performance concrete is between 0 to 25% of the cement mass [9]. By using cement supplementary materials in the aggregate, small particles are introduced in the mix, which strengthens the material and increases its durability as well [10].…”
Section: Literature Reviewmentioning
confidence: 99%